AL-CR-NI ASOSIDAGI YUQORI ENTROPIYALI QOTISHMALARNING MIKROSTRUKTURAVIY, FAZAVIY VA MEXANIK XOSSALARI TAHLILI - Jonuzoqov, Sardor (Techscience uz - Topical Issues of Technical Sciences, 2025)
This paper presents a comprehensive analysis of the phase structure, thermodynamic properties, and microstructural behavior of high-entropy Al-Cr-Ni alloys. The alloy primarily consists of two phases: the ordered B2 (Al-Ni rich) phase and the face-centered cubic (FCC, Cr-Ni rich) phase. These phases act as mutual strengthening components, resulting in hardness values up to 900 HV. Excellent oxidation and heat resistance up to 1200°C are achieved through the formation of protective Al₂O₃ and Cr₂O₃ layers. Heat treatment improves structural stability without significant degradation. Due to their superior thermal and mechanical properties, Al-Cr-Ni alloys are promising candidates for high-temperature turbine blades, nuclear components, and chemical reactors.